Polyphasic characterization of a novel hot-spring cyanobacterium Thermocoleostomius sinensis gen et sp. nov. and genomic insights into its carbon concentration mechanism - Jiang, Ying; Tang, Jie; Liu, Xiangjian; Daroch, Maurycy (Frontiers in Microbiology, 2023)
Thermophilic cyanobacteria are essential primary producers of hot spring ecosystems but are rarely systematically studied at microbiological, taxonomic and ecological levels. Furthermore, molecular-level data and the links between genotypes and phenotypes of these organisms are still scarce despite significant advances in data generation and processing capacity. In this study, we characterized a novel strain of thermophilic cyanobacteria, PKUAC-SCTA174 (hereafter A174) by combining a traditional polyphasic approach with genomic analyses such as internal transcribed spacer secondary structure, 16S rRNA gene phylogenetics, and modern genomics. The results of the 16S rRNA, 16S-23S ITS secondary structure, morphology and habitat analyses support that the strain is a member of a novel genus within the family Oculatellaceae closely related to Albertania and Trichotorquatus. The high-quality genome of the strain was obtained using a hybrid sequencing approach, and phylogenomic inference, and its genomic similarity parameters were determined, those genome-based evidence further confirmed that A174 belong to a novel genus within Synechococcales. Combining traditional approaches and genome-based molecular methods supported the delineation of the strain as Thermocoleostomius sinensis based on the botanical code. The analysis of the complete genome sequence of the strain revealed a sophisticated carbon-concentrating mechanism (CCM) encompassing a full gene complement of bicarbonate transporters: two putative inducible BCT1-type transporters, a constitutive bicA, an inducible sbtA, and two CO2 uptake complexes NDH-I3 and NDH-I4. Interestingly two distinct putative carboxysomal carbonic anhydrases (ccaA1 and ccaA2) were also identified. CCM gene expression was studied with a CO2 shift experiment. High-affinity carbon uptake systems, most notably NDH-I3, sbtA and cmpA showed the largest increase in transcript abundance. Lower affinity systems i.e. bicA and NDH-I4 showed lower. Carboxysome proteins exhibited a temporary drop in expression levels, but recovered after 24 hours. Carbonic anhydrase ccaA1 had higher expression than ccaA2, indicating potentially different cellular localization or role. Finally, the complete genome of strain A174 provides valuable insights into the genetic characteristics of the genus Thermocoleostomius and closely related organisms. The findings of this study help to resolve taxonomic situation within Oculatellaceae and present valuable data that can be utilised for future research in the fields of taxogenomics, ecogenomics, and geogenomics.